Teacher Thinking Process in Providing Scaffolding in the form of Questions in Mathematics Learning - Yayuk, Erna; Deviana, Tyas; Wahyuni, Indah (University of Muhammadiyah Malang, 2024)
Two things must be considered to realize teacher professionalism: the teacher's thinking process and actions. These two things are very important and influence each other. The teacher's activity in providing scaffolding for students' questions is an action that certainly requires a thinking process. Among the research that has been carried out is teacher actions in providing scaffolding; however, there is no disclosure of teachers' thinking processes in helping students with difficulties in solving numeracy questions. Implementing questioning scaffolding in learning will help teachers create better learning and enrich the body of knowledge. This research reveals how the teacher's thinking process is predominantly contingent when scaffolding questions to students. This research uses scaffolding of teachers' thinking processes, which has never been researched before. This research uses a qualitative approach (grounded theory design), which is carried out in the context of mathematics learning. The research subjects were two teachers with dominant analytical contingent (GA) and intuitive contingent dominant (GI) characteristics. These two subjects were selected based on the results of very long observations of 12 teachers in Malang Raya, and only two met the research criteria. In general, it can be concluded that optimizing students' abilities to solve problems can be stimulated through the teacher's thinking process in providing scaffolding in the form of questions in mathematics learning.